The Impact of Oral Probiotics on Laboratory Parameters in Patients With Alcohol Toxicity: A Single-blinded Intervention Study - Tajdari, Mahnaz; Amiri, Farbod; Rahimi, Mitra; Ohadi, Laya; Ghorbani, Fariba; Shadnia, Shahin; Talab Evini, Peyman Erfan (International Journal of Medical Toxicology and Forensic Medicine, 2024)
Background: Alcohol toxicity is a significant medical emergency with implications for patient management and outcomes. This single-blinded randomized intervention study investigated the effects of oral probiotics on various laboratory parameters in patients with acute alcohol toxicity. Methods: A total of 30 eligible patients were randomly assigned to either the control (placebo) or intervention (oral probiotics) group. Results: While the study did not reveal a significant impact on the length of hospital stay (LOHS), it did demonstrate notable improvements in laboratory variables, including pH, serum glutathione level, serum vitamin B6 level, and O2 saturation, in the probiotic group. Conclusion: These findings suggest the potential benefits of probiotics in mitigating certain aspects of alcohol toxicity.